2005
DOI: 10.1227/01.neu.0000144842.18771.30
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Intraoperative Diffusion Tensor Imaging-based Fiber Tracking in Glioma Surgery

Abstract: Comparing preoperative and intraoperative fiber tracking visualizes a marked shifting and deformation of major white matter tracts because of tumor removal. This shifting emphasizes the need for an intraoperative update of navigation systems during resection of deep-seated tumor portions near eloquent brain areas. Fiber tracking is a method not only for preoperative neurosurgical visualization but also for further intraoperative planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
168
0
15

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(189 citation statements)
references
References 42 publications
6
168
0
15
Order By: Relevance
“…15, [73][74][75]105,106 However, the reconstruction of subcortical fiber tracts from diffusion tensor vectors is a purely anatomical imaging analysis that does not include true electrophysiological functional data.…”
Section: Technical Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…15, [73][74][75]105,106 However, the reconstruction of subcortical fiber tracts from diffusion tensor vectors is a purely anatomical imaging analysis that does not include true electrophysiological functional data.…”
Section: Technical Detailsmentioning
confidence: 99%
“…2,5,8,73,78,106 Various studies have investigated the accuracy of pre-and intraoperative DTI-FT compared with intraoperative SCS mapping of the motor pathways, which revealed mostly good intraoperative correlations of DTI-FT and SCS, depending on intraoperative brain shift. 78,81,127,128 The sensitivity of CST detection was 95% in a series by Bello et al, 6 and the sensitivity was 93% at a specificity of 93% in a series by Zhu et al Several reports have shown that especially in LGGs, fibers were frequently located inside the tumor, and DTI-FT was able to visualize these fibers.…”
Section: Current Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using low-field imaging had already shown that complications, such as intraoperative bleeding could be demonstrated using ioMRI [20]. With the use of high-and ultrahigh-field ioMRI, intraoperative diffusion tensor imaging was also performed to visualize the corticospinal tract [21,22]. All of these technologies are still being validated, investigated further and undergoing refinement, and their impact on long-term patient outcome and quality of life still needs to be investigated.…”
Section: Necmettin Pamir MD Editorial Pamir and öZdumanmentioning
confidence: 99%
“…The conclusions after 10 years of experience with ioMRI for neurosurgery are as follows [2,5,8,9,11,13,14,17,[21][22][23][24][25][26]. Current ioMRI technology has very high anatomical resolution but also provides functional information (e.g., functional MRI, DWI, magnetic resonance spectroscopy, diffusion tensor imaging, magnetic resonance angiography and magnetic resonance venography).…”
Section: "Current Intraoperative Mri Technology Has Verymentioning
confidence: 99%